Rare cutaneous metastasis from sarcomatoid carcinoma of lung. Issue 3 (10th March 2021) - Tollan, Clare Josephine; Moyes, Colin; Malyon, Andrew
Abstract : We present the case of a 57-year-old woman diagnosed with stage 4 sarcomatoid carcinoma of the lung who concurrently developed a scalp lesion, thought to be a cyst, which continued to grow and ulcerate. Excision revealed a rare case, only four previously reported in the literature, of metastatic sarcomatoid carcinoma of the lung. While a very unusual case, we would like to emphasise the importance of considering skin metastases when presented with unusual skin lesions, and importantly listening to the patient's concerns, showing empathy and respecting their autonomy and referring to an appropriate specialist when considering the management of what may seem to be a minor skin report.